2015
DOI: 10.1016/j.nmd.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sodium current properties contribute to cardiac electrical and contractile dysfunction in a mouse model of myotonic dystrophy type 1

Abstract: Myotonic dystrophy type 1 (DM1) is the most common neuromuscular disorder and is associated with cardiac conduction defects. However, the mechanisms of cardiac arrhythmias in DM1 are unknown. We tested the hypothesis that abnormalities in the cardiac sodium current (INa) are involved, and used a transgenic mouse model reproducing the expression of triplet expansion observed in DM1 (DMSXL mouse). The injection of the class-I antiarrhythmic agent flecainide induced prominent conduction abnormalities and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
6
17
0
Order By: Relevance
“…The deletion causes a depolarizing shift in both steady-state activation and inactivation (Camacho et al, 2006) similar to that observed for myocytes from LC15 mice and a slowing of Na channel recovery from inactivation (Walzik et al, 2011). Interestingly, inclusion of adjacent Scn5a exon 18 is developmentally regulated and mis-spliced and maximal dV/dt is reduced in DMSXL mice (Algalarrondo et al, 2015). However, baseline QRS duration is not prolonged and Na channel recovery from inactivation is accelerated in DMSXL mice.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion causes a depolarizing shift in both steady-state activation and inactivation (Camacho et al, 2006) similar to that observed for myocytes from LC15 mice and a slowing of Na channel recovery from inactivation (Walzik et al, 2011). Interestingly, inclusion of adjacent Scn5a exon 18 is developmentally regulated and mis-spliced and maximal dV/dt is reduced in DMSXL mice (Algalarrondo et al, 2015). However, baseline QRS duration is not prolonged and Na channel recovery from inactivation is accelerated in DMSXL mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are some similarities of ECG recording, including prolongation of the PR interval and of the QRS duration, between individuals with DM and individuals affected by cardiac-conduction disease caused by loss-of-function mutations in SCN5A 42 54 . Finally, the induction of abnormal ECG pattern in DM patients treated with ajmaline 55 56 , a class Ia antiarrhythmic agent acting on the cardiac sodium channel and the abnormal sodium current observed in a mouse model of DM 57 , are also evocative of a dysfunction of the sodium channel in DM. Overall, our results suggest that misregulation of the splicing of SCN5A participates in a subset of electrical cardiac alterations observed in DM, namely the cardiac-conduction delay and the heart arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, prevalence of Brugada type 1 ECG pattern have been reported in DM1 patients, implicating the role of Brugada syndrome in tachyarrhythmias and cardiac death [181, 182]. The cardiac electrical and contractile phenotype of DM1 has been studied using a mouse model; this constitutively expresses the human DM1 locus under the regulation of its own promoter and cis-regulatory elements, after flecainide treatment [183]. The altered I Na in this mouse model was suggested to be the cause of reduced cellular excitability [183].…”
Section: Modeling Conduction System Defects (Csds): Dm1 Case Studymentioning
confidence: 99%
“…The cardiac electrical and contractile phenotype of DM1 has been studied using a mouse model; this constitutively expresses the human DM1 locus under the regulation of its own promoter and cis-regulatory elements, after flecainide treatment [183]. The altered I Na in this mouse model was suggested to be the cause of reduced cellular excitability [183]. Furthermore, function and localisation of Cl - channel (PLM) is also modulated by DMPK, suggesting that DMPK is involved in EC coupling in muscle cells [184].…”
Section: Modeling Conduction System Defects (Csds): Dm1 Case Studymentioning
confidence: 99%